Early recognition of coeliac disease through community pharmacies: a proof of concept study - Urwin, Heidi (Int J Clin Pharm, 2016)
Setting Fifteen community pharmacies in the UK. Objective Proof of concept study to test the use of community pharmacies for active case finding of patients with coeliac disease. Methods Customers accessing over-the counter and prescription medicines indicated in the treatment of possible symptoms of coeliac disease over a 6 month period were offered a free point of care test. All patients were given advice regarding the test results and those who tested positive were advised to make an appointment with their general practitioner. Patients and pharmacists involved in service provision were asked to complete a satisfaction survey. Pharmacists were additionally invited to undertake interviews to better understand their views on the service. Main outcome measures Feasibility of service, acceptability to stakeholders and proportion testing positive for coeliac disease. Results Of the 551 individuals tested, 52 (9.4 %) tested positive. 277 (50.3 %) were tested for accessing irritable bowel syndrome treatment, 142 (25.8 %) due to presenting for diarrhoea. The proportion of patients testing positive with different symptoms or for different treatments were similar. Of 43 customers who returned the satisfaction survey, all would recommend the service to others, believing the community pharmacy to be a suitable location. Community pharmacists believed that it enabled them to improve relationships with their customers and that medical practices were receptive to the service. Conclusion This proof of concept study has shown that community pharmacies using a point of care test can effectively recognise and refer patients for confirmatory coeliac disease testing with high levels of customer and service provider satisfaction.